Empowerment of Police Personnel in Supporting the Implementation of Electronic Traffic Law Enforcement (ETLE) At the Traffic Directorate of Polda Metro Jaya - Kurniawan, Beni; Suwandi, Made (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Public service given to people is a reflection of professionalism in the state apparatus and a form of compassion and pride in developing the civilization of a nation. This research analyzes the empowerment of Police personnel to support the implementation of Electronic Traffic Law Enforcement (ETLE) in the Directorate of Traffic in Metro Jaya Regional Police. Research used the qualitative methodology with interview and document review. Result of this research shows that ETLE has been conducted well, but there was still mistake in its implementation, in which the analysis was conducted by the ETLE officers, because amount of the officer was not proportional to the ETLE camera, thus causing the mistake in conducting analysis. ETLE implementation can be professional, accountable, and optimal provided that it is supported with human resource in the Indonesian National Police as the main actor in providingsuch service. To realize competent human resource for ETLE personnel, it uses the human resource empowerment strategy for several aspects, namely capability, smoothness, consultation, cooperation, guidance, and support. Empowerment for the traffic personnel involved in ETLE task force must be definitely supported by providing training and simulation continously. Besides, it needs more personnel to match with ETLE cameras that are continuously added. Situation of the work environment that is more open needs to be created to realize competent, accountable personnel.